Ride comfort performance of a vehicle using active suspension system with active disturbance rejection control - Faried Hasbullah, Faried Hasbullah; Faris, Waleed Fekry; Ridhuan Siradj , Fadly Jashi Darsivan; Abdelrahman, Mohammad (Inderscience Publishers, 2015)

(untitled)
Active disturbance rejection control (ADRC) for a quarter-car active suspension system is proposed. The performance of ADRC is compared with benchmark (LQR control) from current literature. A simulation experiment is performed to investigate the performance of ADRC in comparison with passive system and the LQR control, as well as to test the ability of ADRC to cope with varying process. Results show that ADRC performs better than the benchmark control and is able to cope with varying process commonly seen in active suspension system.